The Implementation of English Conversation Program in Elementary School at Rural Area - Nikmatillah, Murni; Megawati, Fika; Astutik, Yuli (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
This article discusses how to participate in Teaching campus programs and implementing English conversation programs in rural areas. Because English is one of the subjects considered difficult by elementary school students, especially in rural areas, teachers need to be active and communicative in giving instruction. This research was conducted in an elementary school at rural areas, This study used the self-study method, in which data are taken from observations and interviews with and English teacher in the school to find out the difficulties or challenges in teaching and learning in rural areas at Tulungagung East Java, Therefore, the self-study researcher is not the self who does the research, but rather the self being studied, not that the self is the only focus. This progression in self-study characterizes teaching as well. So after that, the author compiled this conversation program. The method used in the implementation of this conversation program was the appropriate TPR (Total Physical Response) method to support challenges or difficulties in teaching and learning. This program was carried out once every 2 weeks and was only attended by class 5. And to find out the improvement of students after joining this program, the researcher give assessment. When this activity was carried out the students were very enthusiastic and understood the lessons that I given, many improvements were obtained by them such as word pronunciation, word spelling, vocabulary knowledge, and word composition. This study strongly recommended that TPR is needed to learn English in rural area.